Level of Awareness and Challenges in the Implementation of ISO 9001: 2015 in Laguna State Polytechnic University - Siniloan Campus - Balahadia, Francis Fernandez; Dalugdog, Wilfredp (Asian Journal of Multidisciplinary Studies, 2021)
This study aimed to determine the level of awareness of the respondents to the main functions of the organization’s quality management system, and challenges in the implementation of ISO 9001: 2015 in Laguna State Polytechnic University (LSPU) – Siniloan Campus. Likewise, correlation of the profiles of the respondents to the level of awareness and challenges in the implementation of ISO 9001: 2015 in LSPU. The study used a descriptive research design and a convenience sampling technique with a total of 100 survey participants from Senior Officials, Professors, Faculty, and Non-Faculty personnel. To collect responses, the researchers adapted a structured survey questionnaire used in this study and programmed it in Google Forms. Descriptive statistics such as frequency count, percentage, and weighted mean were used to analyze the extracted data. The spearman rho was used for data inferential analysis. Findings show that employees' level of awareness to the function of ISO 9001:2015 are Fully Aware and Aware, particularly in terms of "ISO support of quality mission, vision, and objectives," with a weighted mean of 4.25 it demonstrates that LSPU employees are fully aware that ISO supports the university's quality mission, vision, and objectives. Employees, on the other hand, “Disagree” with the various listed challenges in the implementation of ISO 9001: 2015. Furthermore, relationship between the profile of the respondents to the level of awareness and challenges in the implementation of ISO 9001: 2015 in LSPU resulted to “no significant relationship”. Researchers conclude that while LSPU employees are generally aware of the key tasks of the university's quality management system, they disagree on the challenges of its implementation. Information dissemination should be done on a regular basis. Furthermore, LSPU employees must internalize the mission, vision, and objectives of the university's quality management system.